2013
DOI: 10.4103/0028-3886.125409
|View full text |Cite
|
Sign up to set email alerts
|

Mobile floating carotid plaque in a young woman

Abstract: A 32-year-old white woman presented with acute onset of right limb weakness, 3 days before hospitalization. She had non-regulated hyperthyreoidism and a history of smoking. Brain computed tomography (CT) showed a several occipital and high parietal ischemic lesions of the left hemisphere [ Figure 1a and b]. Duplex ultrasonography scan (DUS) showed the existence of fibrolipid plaque located on the back wall of the common carotid artery, that extended to the external as well as internal carotid artery making an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Meanwhile, for symptomatic lesions specifically described as mobile plaques, Ko et al, reported two cases with symptomatic MAP that were treated with ticlodipine 200mg daily [6,7]. Similar to the case that is presented here, follow up post one year in Ko et al, showed disappearance of floating plaque [7,8]. Granted that our patient can be classified as symptomatic, it is evident that medical management was both logical and sufficient.…”
Section: Resultssupporting
confidence: 69%
“…Meanwhile, for symptomatic lesions specifically described as mobile plaques, Ko et al, reported two cases with symptomatic MAP that were treated with ticlodipine 200mg daily [6,7]. Similar to the case that is presented here, follow up post one year in Ko et al, showed disappearance of floating plaque [7,8]. Granted that our patient can be classified as symptomatic, it is evident that medical management was both logical and sufficient.…”
Section: Resultssupporting
confidence: 69%
“…Several cases of plaque regression achieved by medical treatment alone including oral antithrombotic drugs have been reported 12,13) ; however, mobile plaques are accompanied by a pathologically degenerated arteriosclerotic flap, and ruptured plaques are accompanied by a mobile thrombus, intimal dissection, thin or defective fibrous capsule, lipid-rich necrotic core, and hemorrhage, and have been treated by CEA in many cases. [2][3][4][5]14,15) However, CAS may be a treatment choice for carotid artery stenosis patients with a past medical history specified as a risk factor for CEA in the stenting and angioplasty with protection in patients at a high risk for endarterectomy, 16) mobile plaques accompanied by clinically significant cardiac disease, severe pulmonary disease, contralateral carotid artery occlusion, contralateral laryngeal nerve palsy, previous radical neck surgery or radiation therapy to the neck, recurrent stenosis after endarterectomy, and age of 80 of vulnerable plaques using optical coherence tomography, and confirmed that the CASPER stent significantly reduced the incidence and volume of PP, suggesting it to prevent embolic complications of vulnerable plaques. 22) The CASPER stent, GORE Carotid Stent, and CGuard have achieved favorable early treatment outcomes in clinical studies performed in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of plaque regression achieved by medical treatment alone including oral antithrombotic drugs have been reported 12 , 13) ; however, mobile plaques are accompanied by a pathologically degenerated arteriosclerotic flap, and ruptured plaques are accompanied by a mobile thrombus, intimal dissection, thin or defective fibrous capsule, lipid-rich necrotic core, and hemorrhage, and have been treated by CEA in many cases. 2 5 , 14 , 15) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation